Home monitoring system (HMS) using Raspberry Pi model B / Faten Fatehah Rosli and Ahmad Yusri Dak - Rosli, Faten Fatehah; Dak, Ahmad Yusri (UiTM Cawangan Perlis, 2017)
Nowadays, numbers of robbery crime keeps increasing as reported by Royale Malaysian Police(RMP) which usually occurs in daylight and also when the owner is not around. This scenario makes the people feel unsafe when leaving their properties since there is a limited monitoring system available. As the current surveillance system needs larger space, expensive and unreliable hence most people usually don't care with their belonging anymore. Besides, if the person does not have a proper security system, their belongings become the target of crime. Thus, HMS is proposed and developed to cater the security issues related to home security. It is designed with condition such as signal is recorded as the intruder move near a motion sensor. Motion sensor generated a TRUE input that detected a signal based on the moving object. Raspberry Pi model B is proposed as a server that responsible to send data directly to database thus the owner can view and easily identify the entity of the moving object when the data recorded via web application. Experimental results showed the ability of the motion sensor to detect movement increase when the distance of movement at the area of sensor decreases. Does, some recommendation had been made in order to improve the performance of the system detection.